The Immune Response Modifier Imiquimod Requires STAT-1 for induction of Interferon, Interferon-Stimulated Genes, and Interleukin-6 - Bottrel, Renata L. A. (American Society for Microbiology, 1999)
Imiquimod is an oral inducer of interferon (IFN) and several other proinflammatory cytokines and has been successfully used topically as an antiviral agent for the treatment of genital warts. We have investigated the molecular mechanisms by which imiquimod induces the expression of IFNs, IFN-stimulated genes (ISGs), and proinflammatory cytokines in vivo, using mice deficient in various components of the IFN signaling system. Mice deficient in the transcription factor interferon regulatory factor 1 (IRF-1) or in the serine/threonine protein kinase PKR responded normally to imiquimod, producing high levels of circulating IFN and induction of several ISGs. On the other hand, when mice deficient in STAT-1 were treated, a 32-fold reduction in the level of circulating IFN was observed, together with a lack of induction of 2-5 oligo adenylate synthetase (2-5 OAS) and IRF-1 genes. Interestingly, there was also a lack of induction of interleukin-6 (IL-6) gene expression, although tumor necrosis factor was induced and readily detected in serum. In mice deficient in the type I IFN receptor, imiquimod induced levels of IFN similar to those in control mice, but again, neither 2-5 OAS, IRF-1, nor IL-6 genes were induced in mutant mice. Our results suggest that STAT-1 plays a critical role in the mechanism of gene activation by imiquimod. Moreover, induction of IL-6 gene expression appears to be dependent on components of the IFN signaling cascade.